Expropriation risk and FDI in developing countries: Does return of capital dominate return on capital? - M. Akhtaruzzaman; Nathan Berg; Christopher Hajzler (Bank of Canada, 2017)
Previously reported effects of institutional quality and political risks on foreign direct investment (FDI) are mixed and, therefore, difficult to interpret. We present empirical evidence suggesting a relatively clear, statistically robust, and intuitive characterization. Institutional factors that affect the likelihood of an abrupt and total loss of foreigners' capital (i.e., return of capital) dominate those that affect rates of return conditional on a strictly positive terminal investment value (i.e., return on capital). A one-standarddeviation reduction in expropriation risk is associated with a 72 per cent increase in FDI, which is substantially larger than the effects of any other dimensions of institutional quality simultaneously controlled for in our empirical models of FDI inflows. This evidence is consistent with the predictions of a standard theory of FDI under imperfect contract enforcement. We show in the context of a simple model with endogenous expropriation that, when there is a binding threat of expropriation, foreign investors can become unresponsive to differences in other dimensions of institutions and political risk, and may even reduce optimal investment as these institutions improve.
Keywords: D23; F21; F23; 330; Development economics; International financial markets